The results of the use of the automated station of weather “Troposphere” in the conditions of the Ukrainian Antarctic Vernadsky Station - S.V. Klok; V. M. Kotsiuba (Ukrainian Antarctic Journal, 2014)
In the articler the comparative analysis of the observational data of the automated weather stations MAWS and "Troposphere", performed with 5 min increments, for the observation period from January 2012 to June 2013. The results suggest a rather high reliability of the new equipment "Troposphere" and the possibility of future use in Ukrainian Antarctic station Akademician Vernadsky.